Molecular Mechanism and Structure-activity Relationship of the Inhibition Effect between Monoamine Oxidase and Selegiline Analogues - Yang, Chuanxi; Wang, Xiaoning; Gao, Chang; Liu, Yunxiang; Ma, Ziyi; Zang, Jinqiu; Wang, Haoce; Liu, Lin; Liu, Yonglin; Sun, Haofen; Wang, Weiliang (Current Computer - Aided Drug Design, 2024)
Introduction: To investigate the inhibition properties and structure-activity relationship between monoamine oxidase (MAO) and selected monoamine oxidase inhibitors (MAOIs, including selegiline, rasagiline and clorgiline). Methods: The inhibition effect and molecular mechanism between MAO and MAOIs were identified via the half maximal inhibitory concentration (IC50) and molecular docking technology. Results: It was indicated that selegiline and rasagiline were MAO B inhibitors, but clorgiline was MAO-A inhibitor based on the selectivity index (SI) of MAOIs (0.000264, 0.0197 and 14607.143 for selegiline, rasagiline and clorgiline, respectively). The high-frequency amino acid residues of the MAOIs and MAO were Ser24, Arg51, Tyr69 and Tyr407 for MAO-A and Arg42 and Tyr435 for MAO B. The MAOIs and MAO A/B pharmacophores included the aromatic core, hydrogen bond acceptor, hydrogen bond donor-acceptor and hydrophobic core. Conclusion: This study shows the inhibition effect and molecular mechanism between MAO and MAOIs and provides valuable findings on the design and treatment of Alzheimer's and Parkinson's diseases.
Keywords: neurological disorders